BARIUM AND STRONTIUM UPTAKE INTO LARVAL PROTOCONCHS AND STATOLITHS OF THE MARINE NEOGASTROPOD KELLETIA KELLETII - Zacherl D.C.; Paradis G.; Lea D.W. (My University, 2003)
The trace elemental composition of calcified larval hard parts may serve as useful tags of natal origin for invertebrate population studies. We examine whether the trace metal barium (Ba) deposits into the calcium carbonate matrix of molluscan larval statolith and protoconch in proportion to seawater Ba concentration at two temperatures (11.5 and 17°C). We also examine strontium (Sr) uptake as a function of temperature. Using encapsulated larvae of the marine gastropod, Kelletia kelletii, reared in the laboratory under controlled conditions, we demonstrate a significant inverse effect of temperature and a positive effect of seawater Ba/Ca ratio on Ba incorporation into larval carbonates. Ba/Ca partition coefficients (DBa) in protoconch were 1.13 at 11.4°C and 0.88 at 17.1°C, while DBa in larval statolith measured 1.58 at 11.4°C and 1.29 at 17.1°C. Strontium incorporation into statoliths is also inversely affected by temperature, but there was a significant positive effect of temperature on Sr incorporation into protoconch. These data suggest larval statoliths and protoconchs can meaningfully record variation in seawater physical and chemical properties, and, hence, have potential as natural tags of natal origin.